Pengembangan Media Konseling Berbasis Platform Digital Sebagai Reading Therapy Dalam Penerimaan Diri - Nurulfitri, Nabilah; Fadhil, Ahmad; Oktara, Tri Windi (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
The Reading Therapy Platform is a digital-based self-acceptance development platform that is easily accessible to all groups, including Generation Z, and can be used anytime, anywhere. In this study, a Reading Therapy Platform for self-acceptance was developed as a source of information and a tool for self-acceptance. The objectives of this study were: (1) to determine the development of the Reading Therapy Platform for self-acceptance and (2) to assess the platform's feasibility based on validation by subject matter, media, and communication experts. This study used a research and development (R&D) method using the Borg & Gall model modified by Sugiyono, which went through five stages. In the product validation stage, the platform was assessed by experts. The validation results indicated that the platform was highly feasible to use, with a good average rating from the experts. The conclusions of this study are: (1) the Reading Therapy Platform received a score of 4.5 and (2) the platform is suitable for use as a self-acceptance platform. It is recommended that all groups, including Generation Z, utilize this platform for self-acceptance.